2006
DOI: 10.1038/sj.bjc.6603178
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR analysis of a 3895 bp mitochondrial DNA deletion in nonmelanoma skin cancer and its use as a quantitative marker for sunlight exposure in human skin

Abstract: Previous findings from our own laboratory have shown that the frequency of occurrence (i.e. the simple presence or absence) of the 3895 bp mitochondrial DNA deletion is increased with increasing sun exposure. The present study has significantly extended this work by developing, validating and then using a quantitative real-time PCR assay to investigate for the first time the actual level (as opposed to the frequency of occurrence) of the 3895 bp deletion in human skin from different sun-exposed body sites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…52 A separate study demonstrated that the actual levels of a specific 3895ebase pair mitochondrial DNA deletion were significantly higher in dermis samples from skin that was usually exposed to the sun compared with samples from skin that was only occasionally exposed (P \.0009). 25 This damage to the mitochondrial genome may impair the capacity for mitochondrial oxidative phosphorylation, which may increase ROS. 25…”
Section: Mitochondrial Dnamentioning
confidence: 99%
“…52 A separate study demonstrated that the actual levels of a specific 3895ebase pair mitochondrial DNA deletion were significantly higher in dermis samples from skin that was usually exposed to the sun compared with samples from skin that was only occasionally exposed (P \.0009). 25 This damage to the mitochondrial genome may impair the capacity for mitochondrial oxidative phosphorylation, which may increase ROS. 25…”
Section: Mitochondrial Dnamentioning
confidence: 99%
“…Photoaging of the skin has been closely tied to mtDNA mutations and deletions (36,53,54), and there is recent evidence associating mtDNA damage with several types of skin cancer (55)(56)(57)(58)(59). A handful of studies that have tested mtDNA from melanoma and non-melanoma skin cancer patients have revealed a number of A 3 G and T 3 C point mutations (56,57,59), often in the context of pyrimidine:pyrimidine dimers.…”
Section: Dna Substrate Thymine Statementioning
confidence: 99%
“…To this end, we initially looked for 2 characteristic mtDNA deletions: (a) the 3895-bp deletion, which is known to occur more frequently in sun-exposed skin and is present in nonmelanoma skin cancer (24), and (b) the 4977-bp deletion, which is known to be involved in neurodegenerative diseases and the processes of aging and photoaging (22,23). As shown in Figure 2C, XPC KD cells accumulated both types of mtDNA deletions in a time-dependent manner.…”
Section: Figurementioning
confidence: 99%